1988
DOI: 10.1042/bj2520349
|View full text |Cite
|
Sign up to set email alerts
|

The oxidation-state-dependent ATP-binding site of cytochrome c. Implication of an essential arginine residue and the effect of occupancy on the oxidation-reduction potential

Abstract: Arg-91 is not part of the active site of cytochrome c that mediates binding and electron transfer, yet it is absolutely conserved in eukaryotic cytochromes c, indicating a special function. The physicochemical properties of analogues are unaffected by the modification of this residue, so they can be used with confidence to study the role of Arg-91. We have established limiting conditions under which this residue alone is specifically modified by cyclohexane-1,2-dione, and have subsequently shown that ATP, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…A high affinity binding site for ATP has been described and shown to involve the invariant Arg 91 (5,(7)(8)(9)(10). The involvement of Arg 91 in binding of ATP and consequent modulation of electron transfer by the protein has been investigated previously by semisynthetic analogs of cyt c in which this single arginine residue of the 66 -104 peptide was chemically modified by cyclohexane-1,2-dione prior to ligation with the 1-65 peptide (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A high affinity binding site for ATP has been described and shown to involve the invariant Arg 91 (5,(7)(8)(9)(10). The involvement of Arg 91 in binding of ATP and consequent modulation of electron transfer by the protein has been investigated previously by semisynthetic analogs of cyt c in which this single arginine residue of the 66 -104 peptide was chemically modified by cyclohexane-1,2-dione prior to ligation with the 1-65 peptide (10).…”
Section: Discussionmentioning
confidence: 99%
“…In cyt c part of the high affinity ATP-binding site is constituted by the invariant Arg 91 (5,(7)(8)(9)(10), and binding of ATP to this decreases the rate of electron flow through the mitochondrial electron transport chain (9). Accordingly, when the ATP-binding site of cyt c is occupied by a covalently bound ATP, the electron-transfer activity of cyt c with reductase and oxidase are inhibited to 41 and 11-15%, respectively, of the values measured for the native protein (3).…”
mentioning
confidence: 99%
“…The choice of smaller cleft incorporating Arg-91 was primarily guided by previous findings that have shown this residue to be critical for ATP binding (11)(12)(13). Also, derivatization of Arg-91 with 1,2-cyclohexanedione blocks the covalent attachment of 8N 3 -ATP (15).…”
Section: Tnp-8n 3 -Amp-irradiationmentioning
confidence: 99%
“…More recently, gel filtration and equilibrium dialysis have indicated that ferroand ferricytochrome c bind two and three molecules of ATP, respectively, at low ionic strength (11,12), and both forms bind one at higher, closer to physiological, ionic strength (13). The binding of ATP is tighter than ADP.…”
mentioning
confidence: 99%
“…In binding to mitochondrial membranes, specific lysines at the A-site or perhaps neighboring the C-site interact with the membrane’s cardiolipin to encourage acyl chain insertion at one or two cavities within the cyt c interior (12, 14, 29). Additionally, cyt c also houses an ATP binding site which includes a group of lysines (Lys72,86,87) and a critical arginine, Arg91 (4, 33). ATP binding to this site has been speculated to coordinate lysines and/or Arg91 needed by cyt c for interaction with respiratory chain partners and with the cardiolipin-containing mitochondrial membrane (5, 14, 34, 35).…”
Section: Discussionmentioning
confidence: 99%